Cohort size and youth unemployment in Europe: a regional analysis - Duncan Roth; John Moffat (European Regional Science Association (ERSA), 2014)
Will the projected decline in the youth share of European countries' populations alleviate the currently high levels of youth unemployment in Europe? Economic theory predicts that in the absence of perfectly competitive labour markets, changes in the relative size of age groups will cause changes in age-specific unemployment rates. In light of the expected development of the youth population's size over the coming decades, this paper utilises heterogeneity in the structure of youth populations across European countries and regions to identify the effect of nationally and regionally defined age-cohort size on the probability of young individuals being unemployed. To account for the possibility that individuals self-select into areas of low unemployment, the empirical analysis employs an instrumental variables estimator to identify the causal effect of age-cohort size. The results show that individuals in larger cohorts are more likely to be unemployed and that the estimated effect is larger when analysis is conducted using less aggregated spatial units. Although the macroeconomic environment is found to be a more important determinant of unemployment probability, shrinking youth cohorts should therefore improve the current youth unemployment situation.
Keywords: J10; J21; R23; 330; Cohort size; unemployment; regional labour markets; causal effect; instrumental variables; EU-SILC